2017
DOI: 10.1515/forj-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration in soil following afforestation of former agricultural land in the Czech Republic

Abstract: Soil organic carbon (SOC) is a great component of the global carbon cycle and plays significant role in terms of climatic changes and agricultural land-use. An important management concern is the extent of SOC stocks sequestration when farmland is converted to forest stands. We have reviewed the literature about changes in SOC stock in relation to altitude and stand age and sought differences between former agricultural land and origin forest stands. Accumulation of SOC was monitored in 17 examples (41 samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
0
14
1
Order By: Relevance
“…Results from various studies on the effects of afforestation on SOC are inconsistent. Some studies have found that afforestation increased SOC accumulation (Lemma et al, 2006;Wang et al, 2011b;Wei et al, 2012;Cukor et al, 2017), whereas other studies have shown that afforestation decreased SOC (Farley et al, 2004;Mao et al, 2010) or there was more initial loss than SOC gain (Paul et al, 2002;Ritter, 2007). In this paper, we did not find any significant changes between poplar shelterbelt plantations and neighboring farmlands.…”
Section: Non-accrual Of Soc Both In Surface and Deep Soil Layers Follcontrasting
confidence: 74%
See 1 more Smart Citation
“…Results from various studies on the effects of afforestation on SOC are inconsistent. Some studies have found that afforestation increased SOC accumulation (Lemma et al, 2006;Wang et al, 2011b;Wei et al, 2012;Cukor et al, 2017), whereas other studies have shown that afforestation decreased SOC (Farley et al, 2004;Mao et al, 2010) or there was more initial loss than SOC gain (Paul et al, 2002;Ritter, 2007). In this paper, we did not find any significant changes between poplar shelterbelt plantations and neighboring farmlands.…”
Section: Non-accrual Of Soc Both In Surface and Deep Soil Layers Follcontrasting
confidence: 74%
“…To determine the differences between plantation forest and neighboring farmlands, many previous studies have looked at a relatively smaller region to minimize the inferences of intersite variation on the forest effects (Mao et al, 2010;Wang et al, 2011b;Wei et al, 2012;Cukor et al, 2017). In the present study, large-scale sampling was undertaken in Songnen Plain (at least 33,000 km 2 ) to determine the general soil change patterns in a 100 cm soil profile.…”
Section: Large Inter-site Variations Closely Associated With Climaticmentioning
confidence: 99%
“…Results from various studies on the effects of afforestation on SOC are inconsistent. Some studies have found that afforestation increased SOC accumulation (Lemma et al, 2006; Wang et al, 2011b; Wei et al, 2012; Cukor et al, 2017), whereas other studies have shown that afforestation decreased SOC (Farley et al, 2004; Mao et al, 2010) or there was more initial loss than SOC gain (Paul et al, 2002; Wang et al, 2006; Ritter, 2007). In this paper, we did not find any significant changes between poplar shelterbelt plantations and neighboring farmlands.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the differences between plantation forest and neighboring farmlands, many previous studies have looked at a relatively smaller region to minimize the inferences of inter-site variation on the forest effects (Mao et al, 2010; Wang et al, 2011b; Wei et al, 2012; Cukor et al, 2017). In the present study, large-scale sampling was undertaken in Songnen Plain (at least 33,000 km 2 ) to determine the general soil change patterns in a 100 cm soil profile.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in SOC and nutrient element content in soil during forest development depend on other factors like previous land use (grasslands, herbaceous plants, etc. ), soil tillage and cultivation, tree species, tree stand age, relief, climate and soil properties like clay content and pH value (Paul et al 2002;Jandl et al 2007;Laganière et al 2010;Uri et al 2014;Cukor et al 2017). Afforestation of agricultural land with deciduous trees like alder (Alnus) species is common in temperate (Anthelem et al 2001) and hemi-boreal biomes of Europe (Uri et al 2011).…”
Section: Introductionmentioning
confidence: 99%